A GPU-based numerical manifold method for modeling the formation of the excavation damaged zone in deep rock tunnels. (February 2020) - Liu, Quanshen; Xu, Xiangyu; Wu, Zhijun
Abstract: In this study, combined with the zero–thickness cohesive element (ZE) model and explicit integration method, a parallelization technique based on graphics processing units (GPU) is proposed to accelerate the computational efficiency of the NMM for modeling the formation of the excavation damaged zone in deep rock tunnels. To optimize the performance of the original NMM when simulating rock masses with fine grains, a ZE model is adopted and a speedup ratio of 41 compared with the original NMM is achieved. To simulate the behavior of the failed rock masses more efficiently and to achieve a higher speedup ratio after parallelization, the explicit integration scheme is introduced to avoid the assembly and solving of linear equations. To further improve the computation efficiency of hardware–based approaches, the GPU–based parallel technique, including a hybrid CPU–GPU framework, a 'single instruction on multiple data' (SIMD) model and a rainbow coloring strategy, is adopted and a speedup ratio of up to 34.7x is achieved. Finally, a series of excavation models are simulated, and the predicted results validate the efficiency and capability of this developed method for modeling the formation of the excavation damaged zone in deeply buried rock tunnels.